Diagnosis and interventional pain management options for sacroiliac joint pain - Ching-Wei Chuang; Sheng-Kai Hung; Po-Ting Pan; Ming-Chang Kao (Tzu Chi Medical Journal)
The sacroiliac (SI) joint is among the most common sources of chronic low back pain, accounting for 15%–30% of patients presenting chronic low back pain. The complex anatomic structures, nerve innervation, and functional biomechanisms of the SI region make it challenging to diagnose and treat the SI joint as a pain source. In addition to physical therapy and medication for treating SI joint pain, multiple interventional measures including steroid injection, radiofrequency ablation, prolotherapy, and SI joint fusion have been proposed with various efficacies. This article describes the etiology, risk factors, and diagnostic methods as well as the different treatment modalities, focusing on interventional pain management options for patients suffering from SI joint pain.